Impact of changes to donor hemoglobin criteria on the rate of donor deferral. Issue 11 (27th September 2018) - Perez, Gabriela E.; Gammon, Richard R.; Whitaker, Barbee I.; Vassallo, Ralph R.; Stubbs, James R.
Abstract : BACKGROUND: The Food and Drug Administration's requirements for "Blood and Blood Components Intended for Transfusion or Further Manufacturing Use" (Final Rule) effective May 2016 changed eligibility criteria for blood donors. A multivariate analysis was performed to measure its impact on donor deferral rates. STUDY DESIGN AND METHODS: Four blood centers submitted data for similar 6‐month periods before and after implementation of the Final Rule. Data included presenting donors, units collected, deferrals, intended products from deferred donors, deferral reasons, presenting donor demographics, donor hemoglobin (Hgb), hematocrit (HCT), pulse, blood pressure (BP), temperature, and other reasons for deferral. Data were aggregated and periods compared. RESULTS: After Final Rule implementation, successful donations decreased by 1.3% (83.1%‐81.9%), despite a 0.2% increase in presenting donors. The rate of Hgb/HCT, pulse, and deferrals increased, while deferrals for other reasons decreased. Male Hgb/HCT deferral rates increased 1.2% (4213 total). Black male donors' Hgb/HCT deferral rate increased (2.7%‐5.2%) but was counterbalanced by an overall 3.7% decrease in black female Hgb/HCT deferrals. While Hgb/HCT deferrals of black donors remained stable overall (17.0% vs. 16.2%), this trend was not observed by all centers. Deferrals for pulse increased (0.2%), as did BP deferrals (0.2%). CONCLUSION: Although there was a small increase in presenting donors after implementation of the Final Rule, there was a decrease in successful donations. While it appeared that deferral in black donors was unchanged, this trend was not observed across all centers. Pulse and BP deferrals rose dissimilarly among centers, according to individual procedures.